A Doença de Alzheimer e suas manifestações na linguagem: um estudo sobre a divulgação científica brasileira e norte-americana à luz da Linguística Cognitiva - Suelen Martins (2019)
In scientific divulgation, which provides clarification to the general public about Alzheimer's disease, a disease that has gained visibility in the contemporary world, cognitive structures such as metaphors, imaging schemes and frames are in favor of the construction of an Idealized Cognitive Model.Thus, this case study aims to investigate two corpora consisting of online scientific articles from Brazil and the US to discover the role of cognitive metaphors and possible image schemas motivated by them related to Alzheimer's disease. One of the specific objectives of this research is to determine which frames are used in the construction of the informative texts and how they serve to express content through lexical items. Finally, we aim to verify which idealized cognitive model underlies the representation about Alzheimer's Disease. The theoretical framework is composed of texts that deal with the notions of conceptual metaphor, Lakoff and Johnson (2003 [1980]), primary metaphor, Grady (1997), idealized cognitive model, Lakoff (1987), Semantic frames, Fillmore (1982), frame and metaphorical construction, Sullivan (2013), frame and Alzheimer's disease, Kirkman (2006), Van Gorp and Vercruysse (2012), Johnstone (2014), and semantic prosody, Louw (2008, 2010) and McEnery and Hardie (2012). Therefore, we created a corpus composed of scientific articles on Alzheimer's Disease, published in Brazilian and North Americans newspapers, collected between January 2011 and July 2017. The data were analyzed with the aid of a metaphorical analysis methodology adapted from Stefanowitschi and Gries (2006), having AntConc tool and Iramuteq software as support methodology for data selection and compilation. Through the findings of this research, we see that the frames are cognitive structures to delineate what aspects of the reality of Alzheimer's Disease should be shown to the public through the newspaper. Predominately, in our corpora metaphors were related. For example, the PLANT and the PUZZLE domains formed DISEASE ICM, military and criminal metaphors from the WAR domain, formed the WAR ICM, and the epidemic metaphors within the EPIDEMIC domain formed EPIDEMIC ICM. The image schemas observed in our corpora were FORCE, CONTAINER, BLOCK and SCALE. From the analysis of the cognitive structures underlying the linguistic expressions, we find a negative semantic prosody, predominant, for instance, in the failed attempt to find the cure, as we also see the use of a positive semantic prosody in other cases, for instance, when found the clues for healing or for treatment. The analysis has shown that you can have culture specific metaphors, namely in the North American corpus, the metaphors included BAD IS DARK, ALZHEIMER'S DISEASE IS PERSON, TIME IS SPACE; in the Brazilian corpus, there are metaphors such ALZHEIMER'S DISEASE IS MOVING OBJECT and EXISTENCE IS VISIBILITY. We deduce that the similarity between the data of the Brazilian and US newspaper occurs because of the influence of the biomedical model, while the difference between the corpora stems from the respective idiosyncrasies of each culture, as was the case with the concept of Alzheimer's disease as dark and time to space metaphors, typical notions of the English language. The US corpus cases were not observed in the Brazilian corpus but, likewise, the Brazilian corpus uniquely represents the disease as an evil, a moving object, visible only when known.